Piauí: brasilidade e memória no jogo discursivo contemporâneo - Carvalho, Pedro Henrique Varoni de (Universidade Federal de São Carlos, 2008)
Supported on Discourse Analysis theoretical references derived from Michel Pêcheux and on the discourse studies proposed by Michel Foucault and Jean-Jacques Courtine, the research aims at following and evaluating the first thirteen editions of Revista piauí, whose first number was released in October, 2006, and at recognizing in this publication the installation of a discursive occurrence. As a hypothesis, we have guided ourselves by the fact that Revista piauí proposes a disruption in contemporary reading practices, which are sometimes characterized by the predominance of pictures and utilization of short objective texts that are addressed to readers who have little time to inquire. Against this order, piauí resists e defines itself as a magazine for those who like to read. The magazine proposes the retaking of literary journalism, which is characterized by long authorial reports. Methodologically, we have selected the linguistic regularities in order to identify the discursive formation the magazine has adopted. We have analyzed, based upon the notion of discursive genre proposed by Bakhtin style, compositional structure and thematic content , the genre subversions and their effects of meaning. In addition, we have also tried to identify Revista piauí resistance fields on themes, language, reading practices. We have considered the concept of resistance as according to Michel Foucault: there is not any single power in society, but a relation of powers and resistances. From this relation among powers and resistances, we have tried to identify the presence of the interdiscourse the discursive memory that penetrates through the new publication. piauí has adopted a 1960 s resistance journalism, which was mainly symbolized by O Pasquim, a weekly publication that reflected Southern Rio de Janeiro city lifestyle. Considering that the nomination piauí refers to the smallest and poorest state of Brazilian Federation and that the new magazine title comes from a Tupi-Guarani-originated expression, some final conclusions assign to the magazine an anthropophagous approach that makes piauí spread Brazility files, and the magazine irruption is linked with a feasible place for the Brazilian experience in the actual context.
Keywords: Resistência cotidiana; Análise do discurso; Antropofagia; Arquivos de brasilidade; Identidade; Piauí; Formação discursiva; Brazility files; Anthropophagy; Identities; Discourse; Discursive formation; Resistance; LINGUISTICA, LETRAS E ARTES::LINGUISTICA